Alcohol and the risk of all-cause death, atrial fibrillation, ventricular arrhythmia, and sudden cardiac arrest - Yun Gi Kim; Dong Yun Kim; Seung-Young Roh; Joo Hee Jeong; Hyoung Seok Lee; Kyongjin Min; Yun Young Choi; Kyung-Do Han; Jaemin Shim; Jong-Il Choi; Young-Hoon Kim (Scientific Reports, 2024)
Abstract The risk of having atrial fibrillation (AF) is associated with alcohol intake. However, it is not clear whether sudden cardiac arrest (SCA) and ventricular arrhythmia (VA) including ventricular tachycardia, flutter, or fibrillation have similar associations with alcohol. We aimed to evaluate the association of alcohol intake with all-cause death, new-onset AF, VA, and SCA using single cohort with a sufficient sample size. A total of 3,990,373 people without a prior history of AF, VAs, or SCA was enrolled in this study based on nationwide health check-up in 2009. We classified the participants into four groups according to weekly alcohol consumption, and evaluated the association of alcohol consumption with each outcome. We observed a significant association between mild (hazard ratio [HR] = 0.826; 95% confidence interval [CI] = 0.815–0.838) to moderate (HR = 0.930; 95% CI = 0.912–0.947) drinking with decreased risk of all-cause mortality. However heavy drinking (HR = 1.108; 95% CI = 1.087–1.129) was associated with increased all-cause death. The risk of new-onset AF was significantly associated with moderate (HR = 1.129; 95% CI = 1.097–1.161) and heavy (HR = 1.298; 95% CI = 1.261–1.337) drinking. However, the risk of SCA showed negative association with all degrees of alcohol intake: 20% (HR = 0.803; 95% CI = 0.769–0.839), 15% (HR = 0.853; 95% CI = 0.806–0.902), and 8% (HR = 0.918; 95% CI = 0.866–0.974) lower risk for mild, moderate, and heavy drinkers, respectively. Mild drinking was associated with reduced risk of VA with moderate and heavy drinking having no associations. In conclusion, the association between alcohol and various outcomes in this study were heterogeneous. Alcohol might have different influences on various cardiac disorders.